Presacral solitary giant neurofibroma without neurofibromatosis type 1 presenting as pelvic mass - Case report - Topsakal, C; Erol, FS; Ozercan, I; Murat, A; Gurates, B (Japan Neurosurgical Soc, 2001)
A 35-year-old woman presented with a solitary neurofibroma in an unusual presacral location without neurofibromatosis manifesting as bilateral chronic sciatica for 2 years. She was initially considered as having a giant right ovarian mass, but was referred with a prediagnosis of solitary giant sacral nerve sheath tumor. The initial differential diagnosis was based on neuroimaging. A right-sided J incision with the extraperitoneal approach provided good exposure and handling of the tumor bed. Almost total excision without neurological deficit was possible. The histological diagnosis was neurofibroma. Benign retroperitoneal neural sheath tumors in patients without von Recklinghausen's disease are quite rare. Intrapelvic tumors are often diagnosed at a later stage. Neuroimaging is very helpful to delineate this unusual site and the extent of tumor development, and to determine the appropriate surgical intervention. A clear understanding of retroperitoneal anatomy is essential for safe removal of such tumors. Complete resection is preferred to prevent local recurrence and malignant transformation. Although root section is inevitable, neurological deficit is unlikely.
Keywords: neural sheath tumor; neurofibroma; pelvic mass; presacral tumors; retroperitoneal tumors